(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Human Resources (HR) are now getting serious attention from the owners of the company. The HR Department begins to be positioned as a strategic unit to determine the direction and policies of the company because the quality of human resources will determine the quality of the policies taken by the company. IT-based Competency-Based Human Resources Management (CBHRM) is a new way of building a reliable human resource information system by utilizing the competences as a central point. This is intended that the companies can improve the effectiveness of recruiting, performance appraisal, training, carrier development, performance management, and strategic planning to the optimum level. The methodology that is used for the implementation of CBHRM is by compiling a competency directory that involves all units in the company with several stages: awareness of CBHRM, Subject Matter Expert (SME) discussion forums, workshops, top-level management forum, and trial. The use of Information System in a Competency-Based Human Resource Management (CBHRM) will simplify the CBHRM complexity process within a company by accelerating the data processing into information that is useful for a decision-maker.